Survival Practices of Children Involved in Child Labor during the Covid-19 Pandemic - Panaligan, Kristine Nicole L. (Animo Repository, 2022)
Surviving the COVID-19 pandemic was a lot harder for low-income families, especially children. Families living in poverty are the most vulnerable to urban shocks and calamities Save the Children Philippines explained that Covid-19 pandemic worsens child poverty that resulted to both parents and children going through lengths to survive leading to child labor. The researchers used a qualitative research design and phenomenological methodology to understand and observe the struggles encountered and survival practices of children involved in child labor during the Covid-19 pandemic. Interviews, observations and discussions were conducted to gather the relevant data and informations. The subjects were three male children and two female children and it was conducted in Brgy. Aldavoc Tagkawayan, Quezon. The result shows that the loss of their parents’ jobs due to the pandemic is the main reason why they had to get a job at a young age. Most of the subjects sold goods at the market, and recycled bottles, plastics, cartons, etc. as their survival practices. On the other hand, the Local Government Unit (LGU) and the Tagkawayan, Quezon Parish Church provided relief goods and financial aid that helped them to make both ends meet daily. The study shows how pandemic affects the daily life of low-income families and calls for possible ways to mitigate the effects of pandemic through community activities that will allow them to earn and provide for their families’ daily needs that will highly affect in lessening the number of children involved in child labor in the community.